124k views
4 votes
If f(x) = x2 - 2x and g(x) = 6x + 4, for which value of x does (f+g)(x) = 0?

2 Answers

3 votes

Answer:

x=-2

Explanation:

f(x) = x^2 - 2x

g(x) = 6x + 4

Add them together

f(x) = x^2 - 2x

g(x) = 6x + 4

-----------------------

f(x) + g(x) =x^2 +4x+4

We want to find when this equals 0

0 =x^2 +4x+4

Factor

What two numbers multiply together to give us 4 and add together to give us 4

2*2 =4

2+2=4

0=(x+2) (x+2)

Using the zero product property

x+2 =0 x+2=0

x+2-2=0-2

x=-2

User Afshin Gh
by
5.3k points
0 votes

Answer:

-2

Explanation:

Let's plug your functions f(x)=x^2-2x and g(x)=6x+4 into (f+g)(x)=0 and then solve your equation for x.

So (f+g)(x) means f(x)+g(x).

So (f+g)(x)=x^2+4x+4

Now we are solving (f+g)(x)=0 which means we are solve x^2+4x+4=0.

x^2+4x+4 is actually a perfect square and is equal to (x+2)^2.

So our equation is equivalent to solving (x+2)^2=0.

(x+2)^2=0 when x+2=0.

Subtracting 2 on both sides gives us x=-2.

User Jhen
by
4.9k points